Hypertension, high-dose corticosteroids, and renal infiltration in children with acute lymphoblastic leukemia - Andry Juliansen; Murti Andriastuti; Sudung Pardede; Rini Sekartini (Paediatrica Indonesiana, 2014)
Background Hypertension is a rarely recognized complication of acute lymphoblastic leukemia (ALL). The incidence of hypertension in ALL patients in Indonesia remains unknown, but the most common risk factors are corticosteroid use during induction-phase chemotherapy and renal leukemic infiltration. Objective To determine the incidence of hypertension in children with ALL, and to assess for associations of high-dose corticosteroids, renal infiltration, and hyperleukocytosis to hypertension. Methods This was a cross-sectional study involving 100 children aged 2-18 years. Subjects were newly diagnosed ALL patients and those underwent induction-phase chemotherapy in the Pediatric Ward or Outpatient Clinic at Cipto Mangunkusumo or Dharmais Hospitals. Results Hypertension occurred in 6 (10%) of 60 newly diagnosed ALL patients and 8 (20%) of 40 patients who had received high-dose corticosteroids, but the difference was not statistically significant (OR=2.25; 95%CI 0.72 to 7.07; P=0.239). Hypertension was reported in 8 of 29 subjects who received dexamethasone, but in none of the subjects who received prednisone. However, the difference in these subgroups was also not statistically significant. Renal enlargement was found in 1 of 14 hypertensive patients, but it was not associated with hypertension (OR=0.80; 95%CI 0.52 to 1.24; P=0.417). Hyperleukocytosis was also not associated with hypertension (OR= 0.79; 95% CI 0.20 to 3.11; P=1.000). Conclusion The incidence of hypertension in ALL patients was 14%. Hypertension is not associated with renal infiltration or hyperleukocytosis. Furthermore, hypertension is not associated with corticosteroid dose, though is found only in subjects who receive dexamethasone. [Paediatr Indones. 2014;54:372-6.].